Consumer Vulnerability After Pandemic Covid-19 on Using Mobile Health Apps - Christina Sudyasjayanti (Publikasi Indonesia, 2024)
This research has highlighted the topic of consumer resilience after the COVID-19 pandemic. This research topic will enhance the subject of Health app users in Indonesia. This research aims to find out the answer to these research questions: the consumer vulnerability caused by the lowest technology literacy, the consumer resilience related to customers’ trust and privacy concerns, and consumer adaptability caused by lack of personalization that will affect purchase satisfaction on Health Apps. Respondents of this research will be limited to 200 people who used Health Apps during 2020-2023. Those respondents will be selected from the four biggest provinces in Java. This research method uses linear regression analysis to determine the influence of consumer vulnerability and consumer resilience toward purchase satisfaction and the moderating effect of consumer adaptability upon consumer vulnerability toward purchase satisfaction and consumer resilience toward purchase satisfaction. The result showed that consumer adaptability did not strengthen the relationship between consumer vulnerability toward purchase satisfaction and consumer resilience toward purchase satisfaction. Alas, each variable significantly affected purchase satisfaction